2011
DOI: 10.1242/dev.065227
|View full text |Cite
|
Sign up to set email alerts
|

Direct targets of theD. melanogasterDSXF protein and the evolution of sexual development

Abstract: SUMMARYUncovering the direct regulatory targets of doublesex (dsx) and fruitless (fru) is crucial for an understanding of how they regulate sexual development, morphogenesis, differentiation and adult functions (including behavior) in Drosophila melanogaster. Using a modified DamID approach, we identified 650 DSX-binding regions in the genome from which we then extracted an optimal palindromic 13 bp DSX-binding sequence. This sequence is functional in vivo, and the base identity at each position is important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 49 publications
1
85
0
Order By: Relevance
“…We attempted to address this question, as described below. Previous work identified regions of likely Dsx DNAbinding activity and a consensus 13-bp Dsx binding motif (GCAACAATGTTGC) (5,13,32). The Lgr3 locus contains three potential Dsx binding sites: a 9/13-bp partial binding site match in R17G11 (GagACAATGTgaC, with mismatches in lowercase), and two 10-and 11-bp partial matching sites in R17H01 (GCAACAtTGaaGt and GttACAtTGTTGC).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attempted to address this question, as described below. Previous work identified regions of likely Dsx DNAbinding activity and a consensus 13-bp Dsx binding motif (GCAACAATGTTGC) (5,13,32). The Lgr3 locus contains three potential Dsx binding sites: a 9/13-bp partial binding site match in R17G11 (GagACAATGTgaC, with mismatches in lowercase), and two 10-and 11-bp partial matching sites in R17H01 (GCAACAtTGaaGt and GttACAtTGTTGC).…”
Section: Resultsmentioning
confidence: 99%
“…The Lgr3 locus contains three potential Dsx binding sites: a 9/13-bp partial binding site match in R17G11 (GagACAATGTgaC, with mismatches in lowercase), and two 10-and 11-bp partial matching sites in R17H01 (GCAACAtTGaaGt and GttACAtTGTTGC). We focused on R17H01 because of its closer matches to the 13-bp motif identified previously (5). We mutated these putative binding sites to disrupt Dsx binding, and hence suggest whether Dsx directly regulates R17H01 expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that the Fmo-2 gene of all five sequenced species in the melanogaster subgroup contained a sequence matching at least 12 bp of the 13-bp optimal DSX-binding site (24). To test whether the conservation of the DSX-binding site at the Fmo-2 gene correlates with conservation of sexually dimorphic Fmo-2 expression, we examined the Fmo-2 expression in six species from the melanogaster subgroup, as well as three species in the melanogaster group but not in the melanogaster subgroup (Fig.…”
Section: Fmo-2 Transcription Is Directly Regulated By Dsx Through Anmentioning
confidence: 99%
“…To fulfill this need, we previously identified potential direct dsx target genes through a genome-wide screen for DSX binding sites (24). Characterization of these candidate genes should facilitate our understanding of the molecular mechanisms and evolution of the differences between males and females.…”
mentioning
confidence: 99%